Intravitreal exposure to the SARS-CoV-2 spike protein is associated with aggravated retinal lesions in a murine model of central retinal vein occlusion - Siyi Liu; Zhihui Zhang; Yumin Zhang; Xinglong Wang; Yibin Yu; Yunshan Cao; Yan Zhang (Frontiers in Medicine, 2026)
Purpose To explore effects of SARS-CoV-2 ocular infection on severity of central retinal vein occlusion (CRVO) and the associated cellular and molecular clues. Methods The spike protein (SP) was intravitreally administered to mimic the pathological process of SARS-CoV-2 ocular infection. Eight-week-old C57BL/6 male mice were randomly divided into 5 groups: normal control (NOR), CRVO, 0.2 SP + CRVO, 0.4 SP + CRVO, and 0.8 SP + CRVO groups. The CRVO group was intravitreally injected with phosphate-buffered saline, and the SP + CRVO groups were intravitreally injected with full-length recombinant SP of Omicron (B.1.1.529) SARS-CoV-2 at 0.2, 0.4, and 0.8 µg. Two days later, a CRVO model was induced via laser photocoagulation following Rose Bengal injection. Then fluorescein fundus angiography (FFA), optical coherence tomography (OCT), and electroretinogram (ERG) were conducted. The retinas from the CRVO and 0.8 SP + CRVO groups were collected on day 9 after modeling for 10× Genomics single-cell RNA (scRNA) sequencing, and the results were validated by immunofluorescence staining of mouse retinas and SP stimulation of a human retinal Müller cell line (MIO-M1). Results In CRVO retinas, FFAs demonstrated reduced intravascular fluorescence dye filling and increased fluorescence dye leakage compared with normal counterparts; OCT revealed edema. Reperfusion was delayed, and the intensity and area of leakage, edema, and electrophysiological functions were significantly aggravated in CRVO retinas pretreated with high-dose SP. ScRNA sequencing revealed dramatically upregulated expression of the Lengsin ( Lgsn ) gene in a Müller cell cluster with a substantially reduced proportion in the CRVO group with SP pretreatment compared with the CRVO group. The gene expression patterns were validated in mouse retinas and MIO-M1 cells. The functional consequences of SP exposure were explored in MIO-M1 cells. Conclusions Intravitreal exposure to SP, the major pathogenic factor of SARS-CoV-2, was associated with delayed vessel reperfusion and exacerbated vascular leakage, edema, and electrophysiological functions in CRVO retinas. ScRNA sequencing revealed that LGSN upregulation in a subpopulation of retinal Müller cells was associated with SP exposure and aggravated retinal lesions in the context of CRVO. These findings may provide molecular and cellular clues for managing SARS-CoV-2-infection-associated CRVO.